On crimes and punishments, and other writings - Beccaria, Cesare (Cambridge texts in the history of political thought, 1995)
This edition of Beccaria's On Crimes and Punishments and other writings presents an interpretation of his thought. Drawing on Italian scholarship, Richard Bellamy shows how Beccaria wove together the various political languages of the Enlightenment into a novel synthesis, and argues that his political philosophy, often regarded as no more than a precursor of Bentham's, combines republican, contractarian, romantic and liberal as well as utilitarian themes. The result is a complex theory of punishment that derives from a sophisticated analysis of the role of the state and the nature of human motivation in commercial society. The translation used in this edition is based on the fifth Italian edition, and provides English-speaking readers with Beccaria's own order of his text for the first time. A number of pieces from his writings on political economy and the history of civilisation which were not previously available in English are also included